1986
DOI: 10.1111/j.1524-4725.1986.tb02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular Effects of Sclerosants in Rabbit Skin: A Clinical and Histologic Examination

Abstract: Sclerotherapy refers to the injection of a material for the purpose of obliterating a blood vessel. During this procedure a small quantity of sclerosing solution may be unintentionally injected into the tissues surrounding the vessel, either by missing the vessel or leakage of sclerosant upon withdrawal of the needle. Occasionally, the sclerosant may be intentionally injected into an extravascular site in the hope of reducing telangiectatic mats (best described as multiple, grouped, extremely fine telangiectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…This phenomenon probably occurs when red blood cells extravasate into the dermis following the rupture of treated vessels 14 . Although Cacciatore 4 has reported a significantly decreased incidence of hyperpigmentation with the use of AES, one of us (DMD) has found the incidence of postsclero‐therapy pigmentation to be approximately equal for SOT, AES, and HS.…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon probably occurs when red blood cells extravasate into the dermis following the rupture of treated vessels 14 . Although Cacciatore 4 has reported a significantly decreased incidence of hyperpigmentation with the use of AES, one of us (DMD) has found the incidence of postsclero‐therapy pigmentation to be approximately equal for SOT, AES, and HS.…”
Section: Discussionmentioning
confidence: 98%
“…Superficial necrosis has been reported to occur frequently at the higher concentration 6,7 . Experimental intradermal injection of 0.5% STS in rabbit skin has also been found to produce epidermal and dermal necrosis both clinically and histologically 8 …”
Section: Introductionmentioning
confidence: 99%
“…Goldman et al. 7 showed that the intradermal injection of 0.1 mL of polidocanol liquid (0.25–1.0%) into the rabbit skin does not produce clinical necrosis. This is consistent with our finding that 0.5 mL is the lowest volume capable of inducing skin necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such deeply situated extravasation is nowadays probably a very rare event considering the ultrasound guidance of sclerosant injection into deeper intrafascial vessels. Goldman et al 7 showed that the intradermal injection of 0.1 mL of polidocanol liquid (0.25-1.0%) into the rabbit skin does not produce clinical necrosis. This is consistent with our finding that 0.5 mL is the lowest volume capable of inducing skin necrosis.…”
Section: Discussionmentioning
confidence: 99%